The prevention as an approach to promoting sanitary safety and sustainability in poultry farming: emphasis on precision nutrition and animal gastrointestinal health - Mendonça, Carlos Miguel Nóbrega (2024)
This thesis is dedicated to the development of scientific research aimed at catalyzing transformative change in pou1try farming. It advocates for the integration of cutting-edge technologies, specialized practices, and innovative product formulations to increase both the productivity and safety ofthe pou1try sector, while promoting environmental management. At the heart of this effort lies the commitment to unravel the complex dynamics of the cecal microbiota of birds, especially broiler chickens (Gallus gallus domesticus), whether through microbial profiles using l6S rRNA V3-V4 sequencing, metagenomic analysis, and large-scale metagenomic sequencing technologies. By exploring the microbial communities inhabiting the cecum of these animais, this study aims to shed light on their profound implications for hea1th and productivity in pou1try farming. The proactive adoption of preventive measures to protect bird health and reduce antibiotic dependency, thus combating bacterial threats, is central to this investigation. Precision nutrition emerges as a fundamental strategy, essential for optimizing intestinal health and strengthening immune resistance in bird populations. The study meticulously explores the subtle interaction between nutrition, environrnental variables, and management practices, advocating for targeted dietary interventions such as probiotics to modulate intestinal microbiota and enhance immune function. Furthermore, this research highlights the importance of the biorefinery as an ecologically sustainable approach to repurpose industrial waste into food additives, thereby promoting sustainability within the industry. By exploring valorization strategies for industrial waste, especially the conversioo of sugarcane bagasse into functional food additives, the study aims to create cost-effective bionutritional products in accordance with the principies of a \"circular bio-nutrient economy.\" Recognizing the transformative potential of these efforts, the research endeavors to develop a modem, resilient, and reliable bio-nutrient supply chain, suited to the demands of an evolving livestock production paradigm. Transitioning to food quality and safety, this study also explores the mitigation of mycotoxins as a fundamental measure to protect the health aod well-being of animal populations, exploriog the developmeot of a biobased approach using bacterial inoculants. Finally, through in vitro experimeots, the research examines the dynamics of chicken intestinal microbiota under the influence of produced fibers and LAB (lactic acid bacteria), seeking to assess their fermentability profile and potential benefits for health, performance, and overall animal productivity. In conclusion, this comprehensive research articulates a futuristic vision for poultry farming, grounded in the principIes of health, sustainability, and efficient resource utilizatioo. Through a multifaceted approach encompassing precision nutrition, preventive measures, biorefinery, and microbial modulatioo, the study aspires to advance sustainable poultry production practices aod promote a more resilient and environmentally conscious agricultural sector.